Changes in whole grain polyphenols and antioxidant activity of six sorghum genotypes under different irrigation treatments. (1st January 2017) - Wu, Gangcheng; Johnson, Stuart K.; Bornman, Janet F.; Bennett, Sarita J.; Fang, Zhongxiang
Highlights: Sorghum grain physical characteristics were influenced by genotype. Polyphenol content and antioxidant activity were affected by sorghum genotype. Sorghum grain physical characteristics were influenced by irrigation treatment. 3-Deoxyanthocyanidin content significantly increased under water deficit regime. Antioxidant activity of sorghum significantly increased under water deficit regime. Abstract: Sorghum grain containing elevated polyphenolic antioxidant content may provide foods with benefits to human health. A study was undertaken to determine the potential role of irrigation on the content of polyphenols and antioxidant levels in sorghum grain. Bound, free and total polyphenols were investigated in six diverse sorghum genotypes grown under either full irrigation or a deficit irrigation regime. Results showed genotype, irrigation and their interaction had a significant effect on polyphenols and antioxidant activity ( P  ⩽ 0.05). The deficit irrigation treatment significantly increased polyphenol content and antioxidant activity compared to the full irrigation treatment. Of the six genotypes Shawaya black short 1 and IS1311C (brown) showed the highest polyphenols levels and antioxidant activity. Therefore, both irrigation treatments and genotype need to be considered by sorghum breeders and farmers during sorghum production to produce grain with the required levels of polyphenolics and antioxidant activity for targeted end-use.